Cell proliferation and volume-weighted mean nuclear volume in high-grade pin and adenocarcinoma, compared with normal prostate - Teba, Fernando (Image analysis and stereology, 2007)
High-grade prostate intraepithelial neoplasia (PIN) is considered a precursor of prostate adenocarcinoma. The aim of this study was to quantitate the differences between basal and luminal cells of PIN in relation to mean nuclearvolume (Vvnuc), and proliferating cell nuclear antigen labeling index (LIpcna), and to compare these estimates with those obtained in normal prostate and carcinoma. The epithelium of both normal and PIN specimens was segmented in basal and luminal compartments, and the Vvnuc and LIpcna measuredin both strata. Vvnuc was significantly lower in normal epithelium than in both PIN and carcinoma. The Vvnuc of basal layer of PIN was significantly higher than in luminal stratum. The luminal Vvnuc was similar inboth PIN and adenocarcinoma. The LIpcna was greater in PIN and adenocarcinoma than in normal glands. The LIpcna of basal cells from PIN was similar to that observed in the basal stratum from normal prostate, whereas the luminal proliferation from PIN was similar to that observed in adenocarcinoma. The similarities in nuclear size between PIN and carcinoma areaccording to the premalignant character of PIN. The increase of basal Vvnucin PIN indicates that the changes heralding the progression from PIN to carcinoma are produced in this layer, whereas the nuclear features of the luminal layer are the same to those of the carcinoma. These remarks make sensein reference to the progression of malignant changes from PIN basal layerto PIN luminal layer and from this to carcinoma.
Keywords: Adenokarcinom; Prostatic Intraepithelial Neoplasia; Adenocarcinoma; Celična delitev; Celično jedro; Cell Division; Cell Nucleus; Prostata, intraepitelijska neoplazija; Slika, obdelava z računalnikom; Image Processing, Computer-Assisted; Immunohistochemistry; Celica, velikost; Imunohistokemija; Cell Size; diagnostika; prostata; prostate; histologija; stereologija